OPTIMALISASI PEMANFATAAN LAHAN PEKARANGAN MENGGUNAKAN TEKNIK VERTIKULTUR UNTUK BUDIDAYA SAYURAN PENCEGAH STUNTING PADA BALITA GIZI BURUK - Angelia, Ika Okhtora; Nurhafnita, Nurhafnita; Akolo, Ingka R (UPPM Politeknik Gorontalo, 2020)
Stunting is a major challenge to the quality of Indonesian people, as well as a threat to the nation's competitiveness. This is because children are stunted, not only hinder their physical growth (short / dwarf), but also improve brain development, which of course will greatly affect the ability and achievement in school, increase and increase productivity in productive periods. Improving diet by starting to plant high substances and folic acid in the yard (Moringa leaves, green spinach leaves and sweet potatoes) are also needed specifically to meet the needs of pregnant women and MPASI toddlers. Farmers' homes to provide vegetables for households. Thus the more easy access to stunting prevention vegetables, the protection against stunting for infants can be calculated the prevalence rate.